Nepal : Proposed Power Sector Development Strategy - World Bank (Washington, DC, 2013)
A major policy objective of the Government of Nepal is to develop its vast hydro power resource potential, to serve electricity needs, and generate export revenue. But, while recent progress has been made in developing regulations, and policies to attract investments for hydropower development, institutional constraints are challenging implementation. The report attempts to analyze key implementation constraints in hydropower development, proposes options for reform, and, notes four prominent key constraints: overlaps in policy, regulatory, and operational functions of public institutions operating in the sector; inadequacies of the existing institutional structure of the National Electricity Authority to meet future needs of the power sector; insufficient institutional arrangements for the promotion of power trade; and, weak institutional support for improving electricity access to rural areas. Recommendations suggest that the role of policy making should rest with the Ministry of Water Resources, having the Department of Electricity Development, and the Water and Energy Commission given the role of executing bodies, while redefining other Departments to evolve as independent regulatory authorities. Elimination of conflict of interest, creditworthiness improvement, and appropriate regulatory framework, should attract private investments, giving an opportunity to create a policy environment for independent power producers, and favorable for medium-sized export projects.